MALE CHARACTER’S GENDER ROLES AND GENDER DEVELOPMENT IN YAOI MANGA AOZORA NO SUNDA IRO WA - Cynthia Sari Sunjaya; Meilinda Meilinda (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
One genre that has been growing rapidly in manga is yaoi, which sells romance between beautiful young boys and men.  In Aozora no Sunda Iro wa, I want to reveal how Sugiura takes female role in his same-sex romantic relationship and why Sugiura has dominant feminine features which leads to his feminine role.  I used gender role theory and attitudinal pathway gender schema theory.  I find out that Sugiura has female-like body-type.  He is neat, supportive, sensitive, innocent, weak, and submissive.  He is motherly and economically dependent.  In addition, Sugiura became feminine because of Fukada’s involvement in Sugiura’s childhood, his masculine value was rejected while he was encouraged to hold feminine value.  In conclusion, Sugiura is a feminine uke by showing feminine qualities in his persona code, emotion code, and action code which are resulted by Fukada’s involvement in his childhood